The Value of fairness : the story of Nellie Bly - Johnson, Ann Donegan (La Jolla, CA : Value Comm., Inc Pub, 1977)
Demonstrates the value of fairness in the life of the turn-of-the-century journalist whose pen name was Nellie Bly.
Keywords: Cocharan, Elizabeth, 1867-1922; Journalists; Fairness